Learning from Women with a Body Mass Index (Bmi) ≥ 30 kg/m(2) who have Breastfed and/or are Breastfeeding: a Qualitative Interview Study - Lyons, Stephanie (Matern Child Health J, 2019)
Objectives Women with a BMI ≥ 30 kg/m(2) are less likely to initiate and maintain breastfeeding compared to women with a BMI ≤ 30 kg/m(2). Reasons for this disparity are not understood. Therefore, this qualitative interview study aimed to learn from women with a BMI ≥ 30 kg/m(2) who have breastfed. Methods Eighteen women participated in a semi-structured telephone interview. Participants were required to have had a BMI ≥ 30 kg/m(2) at the start of their pregnancy, and have breastfed and/or be currently breastfeeding. An inductive thematic analysis was used to analyze data. Results Two themes were identified: ‘personal control over breastfeeding behavior’ and ‘realistic expectations of the breastfeeding journey’. To achieve their breastfeeding goals, women described the importance of feeling in control of their behaviors, and having realistic expectations, when facing social and practical barriers. They gained this control and formed realistic expectations by seeking support and information. In particular, gaining support from other breastfeeding women with a BMI ≥ 30 kg/m(2), and information about alternative positioning, and compatible clothing and nutrition helped women to breastfeed. Conclusions for Practice Having adequate information and support in order to feel in control of breastfeeding behavior and form realistic expectations are vital contributors to breastfeeding behaviors in women with a BMI ≥ 30 kg/m(2). Future work is necessary to develop suitable interventions and to investigate their feasibility.